Final Thoughts: Concluding the Special Issue - Hayley Anne Cannizzo; Graham V. Crookes; Priscila Fabiane Farias; Angela H. Häusler; Priscila Leal; Jayson Parba; Leonardo da Silva; Sávio Siqueira; Gordon Blaine West; Nicole Ziegler (MDPI AG, 2021)
In this final contribution, the authors of the Special Issue reflect collaboratively on the work gathered in the Special Issue [...]